2016
DOI: 10.1007/s10874-016-9344-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of carbonyl-containing α-pinene ozonolysis products using O-tert-butylhydroxylamine hydrochloride

Abstract: The yields of carbonyl-containing reaction products from the ozonolysis of α-pinene have been investigated using concentrations of ozone found in the indoor environment ([O3] ≤ 100 ppb). An impinger was used to collect gas-phase oxidation products in water, where the derivatization agent O-tert-butylhydroxylamine hydrochloride (TBOX) and gas chromatography-mass spectrometry were used to identify carbonyl-containing species. Seven carbonyl-containing products were observed. The yield of the primary product, pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…The former is referred hereafter as the alcohol pathway, and the latter the aldehyde pathway (aldehyde + HSO4 − ; Surratt et al, 2007). Because aldehydes should dominate the products from α-pinene ozonolysis in the presence of an OH scavenger (Gaona-Colmán et al, 2017) and 470 pinonaldehyde has been detected in previous α-pinene ozonolysis studies with an OH scavenger (Jackson et al, 2017), we propose that the aldehyde pathway could be one of the dominant OS formation pathways in this study. In addition to m/z 265, we propose possible aldehyde precursors formed in α-pinene ozonolysis experiments for five other OS compounds identified in this study (i.e., m/z 251, 253, 269, 279, and 283).…”
Section: Os Formation Under Acidic Conditionsmentioning
confidence: 68%
See 1 more Smart Citation
“…The former is referred hereafter as the alcohol pathway, and the latter the aldehyde pathway (aldehyde + HSO4 − ; Surratt et al, 2007). Because aldehydes should dominate the products from α-pinene ozonolysis in the presence of an OH scavenger (Gaona-Colmán et al, 2017) and 470 pinonaldehyde has been detected in previous α-pinene ozonolysis studies with an OH scavenger (Jackson et al, 2017), we propose that the aldehyde pathway could be one of the dominant OS formation pathways in this study. In addition to m/z 265, we propose possible aldehyde precursors formed in α-pinene ozonolysis experiments for five other OS compounds identified in this study (i.e., m/z 251, 253, 269, 279, and 283).…”
Section: Os Formation Under Acidic Conditionsmentioning
confidence: 68%
“…In addition to m/z 265, we propose possible aldehyde precursors formed in α-pinene ozonolysis experiments for five other OS compounds identified in this study (i.e., m/z 251, 253, 269, 279, and 283). Except for the study where the aldehyde precursor of m/z 269 was found (Reinnig et al, 2009), an OH scavenger was used in all other studies where the aldehyde precursors were found 475 (Yu et al, 1999;Ma et al, 2008;Jackson et al, 2017). Presently, we suppose that the other five OS compounds were possibly formed through the alcohol pathway although no relevant information has been found for m/z 247 and 249.…”
Section: Os Formation Under Acidic Conditionsmentioning
confidence: 97%
“…Experiments were performed at 297 ± 3 K and 1 atm in a collapsible 80 L reaction chamber that has been described previously (Ham et al, 2015, 2016; Jackson et al, 2017). Briefly, the collapsible reaction chamber was constructed from 5-mil fluorinated ethylene propylene copolymer (FEP) Teflon film (Welch Fluorocarbon Inc., Dover, NH) and sealed using a W-600T double foot sealer (Sealer Sales, Northridge, CA).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The canister air samples were analyzed using modifications to a previously published gas chromatograph/mass spectrometer method that allowed analysis of diacetyl, 2,3-pentanedione, and 2,3-hexanedione in addition to 17 other VOCs [LeBouf et al 2012]. Area samples to identify terpenes and ozone reaction products, collected alongside the canisters, were analyzed using a previously published derivatization technique [Jackson et al 2016]. An Aeroqual Series 500 portable air monitor with an ozone sensor was used to periodically record ozone concentration throughout the facility.…”
Section: Air Sampling For Vocsmentioning
confidence: 99%
“…For all carbonyl samples, after collection, the water was decanted into 40-mL vials, then 100 microliter (µL) aqueous 250 mM O-tert-butylhydroxylamine hydrochloride was added (TBOX, Sigma Aldrich) [Jackson et al 2016]. After being shipped to the lab, the vials were placed in a heated water bath at 70°C for 2 hours.…”
Section: Terpene and Oxygenated Compoundsmentioning
confidence: 99%